COMPARATIVE LEGAL FRAMEWORK ON FOREIGN WORKERS REGULATION: INDONESIA AND THE DEMOCRATIC REPUBLIC OF CONGO - Komang Gede Pramantara; Ni Gusti Agung Ayu Mas Tri Wulandari; Claude Iguma Wakenge (Kanun Jurnal Ilmu Hukum, 2025)
Foreign workers are an unavoidable global phenomenon, although for developing countries, they can pose challenges related to the availability of jobs related to the local workforce. This study analyzes the comparative legal framework for regulating foreign workers between Indonesia and the Democratic Republic of the Congo. This research is a normative legal study with a conceptual, comparative, and legislative approach. The results emphasize the urgency of regulating foreign workers in developing countries, to achieve proportional and equitable arrangements between the national interests of a country (in this case, local workers) and foreign workers, thereby ensuring fairness, certainty, and benefits. Based on a comparison of the laws regulating foreign workers in Indonesia and the Democratic Republic of the Congo, it can be concluded that Indonesia has a more comprehensive, structured, and normative regulatory framework, while the Democratic Republic of the Congo relies more on pragmatic work permit and visa mechanisms. This study recommends that the regulation of foreign workers in both countries should function not only as an administrative tool and investment attraction, but also as an equitable and responsive instrument to global labor dynamics, contributing to strengthening the rule of law and building national workforce capacity in the context of developing countries facing current economic challenges.